2014
DOI: 10.1088/0965-0393/22/7/075010
|View full text |Cite
|
Sign up to set email alerts
|

Twin nucleation in Fe-based bcc alloys—modeling and experiments

Abstract: We develop an analytical expression for twin nucleation stress in bcc metal and alloys considering generalized planar fault energy and the dislocations bounding the twin nucleus. We minimize the total energy to predict the twinning stress relying only on parameters that are obtained through atomistic calculations, thus excluding the need for any empirical constants. We validate the present approach by means of precise measurements of the onset of twinning in bcc Fe-50at%Cr single crystals showing excellent agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 54 publications
2
17
0
Order By: Relevance
“…However, when the size reduces from the micro to the nanoscale, the material strength increases dramatically, and dislocations become rare . Previous simulations and experiments on nanoscale α‐Fe under tension already showed that twinning dominates …”
Section: Resultsmentioning
confidence: 99%
“…However, when the size reduces from the micro to the nanoscale, the material strength increases dramatically, and dislocations become rare . Previous simulations and experiments on nanoscale α‐Fe under tension already showed that twinning dominates …”
Section: Resultsmentioning
confidence: 99%
“…8. Plasticity via formation of twins has previously been reported for both single crystal [40][41][42][43] and polycrystalline iron [44]. It has been shown, for sc-iron, that twinning occurs as a results of disassociation of [111] core of an (a/2) h111i dislocation into three (a/6) h111i fractional dislocations.…”
Section: Plastic Deformation During the Scratching Stagementioning
confidence: 93%
“…Based on this slip system, the Burgers vector (b) for B19 Ti-6.25Zr-25Nb lattice is equal to 3.24 Å , for example. The GSFE is obtained by shearing one half (001) plane of the crystal with respect to another half by continuous rigid displacements of u x = nb along [100] direction, where b is the magnitude of the Burgers vector and n is a parameter ranging from 0 to 1 [18][19][20]. Similarly, Fig.…”
Section: Slip and Gsfe Curves In B19 Ti-based Alloysmentioning
confidence: 99%